The visual and instrumental analyses of different single-shade resin composites = Análisis visual e instrumental de diferentes resinas compuestas omnicromáticas - Erçin, Özlem; Kopuz, Dilan (2024)
The purpose of this study was to evaluate the color adaptation of single-shade resin composites applied to different tooth shades. A total of 108 class III preparations (n=6) were performed on the acrylic denture maxillary incisors (2mm depth and 2mm height). 5 single-shade resin composites (Vittra APS Unique, Omnichroma, ZenChroma, Clearfil Majesty ES-2 Universal, Charisma Topaz One) and 1 multishade resin composite (Estelite Asteria) were placed in the cavities and polished. I performed visual and instrumental color analyses. The CIEDE2000 formula was used to assess the shade differences (ΔE) between teeth and restorations. The obtained ΔE values were recorded and statistically analyzed. For the instrumental analysis, ZenChroma in A1 shade groups showed statistically significant higher differences (p<0.05). Among all tested materials, A3 shade groups showed lower ΔE values (p<0.05). For the visual analysis, there were no significant differences between materials and scores in A1 and A3 shade groups (p>0.05). There were statistically significant differences between the materials and the scores in A2 shade groups (p<0.05). As a result of this study, it was concluded that, making esthetic restorations with single-shade resin composites promises proper color adaptation, but their properties still need improvement. Single-shade resin composites can reduce chair-time and technical sensitivity with good color matching.
El objetivo de este estudio fue evaluar la adaptación del color de resinas compuestas omnicromáticas. Se realizaron un total de 108 preparaciones de clase III (n=6) en los incisivos superiores de prótesis acrílicas (2mm de profundidad y 2mm de altura). Se colocaron cinco resinas compuestas omnicromáticas (Vittra APS Unique, Omnichroma, ZenChroma, Clearfil Majesty ES-2 Universal, Charisma Topaz One), además de una resina multitono (Estelite Asteria) en las cavidades y se pulieron. Se realizó el análisis de color visual e instrumental. Se utilizó la fórmula CIEDE2000 para evaluar las diferencias de tono (ΔE) entre dientes y restauraciones. Los valores de ΔE obtenidos se registraron y analizaron estadísticamente. Para el análisis instrumental, ZenChroma en los grupos de color A1 mostró diferencias mayores estadísticamente significativas (p<0,05). Entre todos los materiales probados, los grupos de tonos A3 mostraron valores de ΔE más bajos (p<0.05). Para el análisis visual, no hubo diferencias significativas entre materiales y puntuaciones en los grupos de color A1 y A3 (p>0,05). Hubo diferencias estadísticamente significativas entre los materiales y las puntuaciones en los grupos de color A2 (p<0,05). Como resultado de este estudio, se concluyó que la realización de restauraciones estéticas con resinas compuestas omnicromáticas promueve una adecuada adaptación del color, pero aún necesitan mejorar sus propiedades. Las resinas compuetas omnicromáticas pueden reducir el tiempo de atención clínica y la sensibilidad técnica con una adecuada combinación de colores.
En revista Odóvtos, vol. 26, no.1 (enero-abril 2024)
Descripción basada en el contenido visto el 22 de enero, 2025
También disponible en formato HTML y EPUB